A new species of Tricorythopsis Traver, 1958 (Ephemeroptera: Leptohyphidae) from Pará state, Brazil - de Oliveira, Laura A.; Nascimento, Jeane M. C. Do; Couceiro, Sheyla R. M. (Zootaxa, 2021)
A new species of Tricorythopsis is described, illustrated and diagnosed based on nymphs from Pará state, Brazil. Tricorythopsis similis sp. nov. is related to Tricorythopsis rondoniensis (Dias, Cruz & Ferreira) based on abdominal terga III–VII with acute tubercles medially located on posterior margins, and by the absence of the transversal line on operculate gill. However, the new species can be identified by the following combination of characteristics: general coloration yellowish brown, with blackish and purplish marks irregularly distributed; maxillary palp 1-segmented; segment II of labial palp shorter than segment I and longer than segment III; femora and tibiae with margins covered by long, pectinate setae; tarsal claws with 4 to 5 marginal denticles and 4+2 very small, submarginal denticles. This is the first species of Tricorythopsis recorded from Pará state.